He’s frequency formulation for fractal-fractional nonlinear oscillators: a comprehensive analysis - Zhang, Liangyuan; Gepreel, Khaled A.; Yu, Jiahui (Frontiers in Physics, 2025)
This mini-review focuses on He’s frequency formulation for fractal-fractional nonlinear oscillators. It examines the significance and applications of this formulation in understanding and analyzing the frequency-amplitude relationship within a fractal space. The review analyses the key features and advantages of He’s frequency formulation, highlighting its role in providing a straightforward approach to fractal vibration systems compared to traditional methods. Furthermore, it discusses an open problem for future research.